Effectiveness of Australian cooking skill interventions - Begley, Andrea; Gallegos, D.; Vidgen, H. (Emerald Group Publishing Limited, 2017)
© 2017, © Emerald Publishing Limited. Purpose: The purpose of this paper is to assess the effectiveness of cooking skill interventions (CSIs) targeting adults to improve dietary intakes in public health nutrition settings. Design/methodology/approach: A scoping review of the literature was used to identify and assess the quality and effectiveness of Australian single-strategy CSIs and multi-strategy programmes that included cooking for independent healthy people older than 16 years from 1992 to 2015. Findings: There were only 15 interventions (n=15) identified for review and included CSIs as single strategies (n=8) or as part of multi-strategy programmes (n=7) over 23 years. The majority of the interventions were rated as weak in quality (66 per cent) due to their study design, lack of control groups, lack of validated evaluation measures and small sample sizes. Just over half (53 per cent) of the CSIs reviewed described some measurement related to improved dietary behaviours. Research limitations/implications: There is inconclusive evidence that CSIs are effective in changing dietary behaviours in Australia. However, they are valued by policymakers and practitioners and used in public health nutrition programmes, particularly for indigenous groups. Originality/value: This is the first time that CSIs have been reviewed in an Australian context and they provide evidence of the critical need to improve the quality CSIs to positively influence dietary behaviour change in Australia.